A THREE-DIMENSIONAL METHOD FOR CALCULATING INDEPENDENT CHEMICAL U/PB- AND TH/PB-AGES OF ACCESSORY MINERALS - Rhede D.; Wendt I.; Forster H.J. (My University, 1996)
Previous theoretical considerations on the chemical U-Th-total Pb dating method failed to distinguish between thorogenic and uranogenic lead. However, it can be shown that the data points are located on a plane in the three-dimensional ThO2, PbO, UO2 space. The calculation of the best-fit plane yields a slope in the ThO2-PbO and UO2-PbO coordinate projections, and an initial PbO value. From the two slopes, Th/Pb- and U/Pb-ages can be calculated independently.The method described in this paper is applied to monazites from the Hercynian G4-granite of the Fichtelgebirge (Germany). Th/Pb- and U/Pb-ages were calculated at 323 +/- 20 Ma and 304 +/- 15 Ma, respectively. The intercept value close to zero indicates that no significant amounts of common lead are present in the monazites studied.